2008
DOI: 10.1108/17542410810858321
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship and SMEs in Ethiopia

Abstract: Purpose -This paper attempts to identify the problem areas and developmental issues attached to women's entrepreneurship related to small medium enterprises (SMEs) particularly in Addis Ababa, the capital city of Ethiopia. It also attempts to devise certain stratagems for ensuring women's entrepreneurial growth and SMEs' advancement in the region. Design/methodology/approach -The study was conducted in two phases. The first phase attempted to identify the problem areas in terms of nature, needs, desire, motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(36 citation statements)
references
References 13 publications
(8 reference statements)
0
28
0
2
Order By: Relevance
“…However, we found a lack of investigation as regard to new businesses opportunities in the sectors of the green economy, big data management and social media, which gives opportunities for future research. Another relevant topic, which we expect to gain momentum, concerns women entrepreneurs and business network (Brunetto and Farr-Wharton, 2007;Klyver and Terjesen, 2007;Singh and Belwal, 2008;Demartini and Paoloni, 2012). The stream of research concerning differences between women and men includes studies addressing diversity and equality within varying socio-demographic backgrounds and geo-political contexts (Martin, 2006;Holvino, 2008), as well as in academic careers (Probert, 2005) and other professions (Powell et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…However, we found a lack of investigation as regard to new businesses opportunities in the sectors of the green economy, big data management and social media, which gives opportunities for future research. Another relevant topic, which we expect to gain momentum, concerns women entrepreneurs and business network (Brunetto and Farr-Wharton, 2007;Klyver and Terjesen, 2007;Singh and Belwal, 2008;Demartini and Paoloni, 2012). The stream of research concerning differences between women and men includes studies addressing diversity and equality within varying socio-demographic backgrounds and geo-political contexts (Martin, 2006;Holvino, 2008), as well as in academic careers (Probert, 2005) and other professions (Powell et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in developing countries have shown that those with the highest economic growth, such as China, are also the ones where women are highly active in business (Tambunan, 2009). The importance of women entrepreneurs is especially noted in rural areas of Asia and Africa where women's economic participation is highly associated with poverty alleviation (Singh and Belwal, 2008;Woldie and Adersua, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the level and structure of startup capital in SMEs reflects the owners' more tolerant attitudes towards risk. Singh and Belwal (2008) extended this argument and suggested that gender differences in start-up capital are linked to variances in risk appetite, in addition to differences in the entrepreneur's experience of running a firm and in the nature and type of the business. Another stream of the literature stresses that risk attitude is not the key determinant of entrepreneurship, but rather that motivation and capabilities are key factors (Baumol 1990;Kirzner 1973;Knight 1921).…”
Section: Review Of the Literaturementioning
confidence: 99%